The Cult of Corruption: Reframing Organizational Frameworks of Police Corruption from a Cultic Perspective. Issue 5 (4th May 2021) - Bleakley, Paul
ABSTRACT: Corruption in policing is a criminological phenomenon that is regularly misconstrued – whether as a case of independently-operating "rotten apples" or as a passive symptom of anomic organizational culture. This article seeks to reframe organized police corruption as an active process of seductive-recruitment, wherein corrupt officers utilized the same strategies as a conventional cult to both recruit and retain members. Using the example from Australia of the Queensland Police Force in the era before the Fitzgerald Inquiry as its primary case study, this article draws on a range of cult studies theories to develop an innovative framework for understanding the process by which an officer is lured into organized corruption. It discusses the intrinsic and extrinsic motivators for this in-group affiliation, with reference to matters of role and identity that derive from involvement with the "blue brotherhood" of policing. In casting organized police corruption as a form of secular cult, it provides an opportunity to better understand the tactics used to entrap new members into corrupt networks, as well as to consider the factors that make them vulnerable to recruitment in the first place.